2014
DOI: 10.1371/journal.pone.0084416
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Copper Homeostasis and Biotic Interactions by MicroRNA 398b in Common Bean

Abstract: MicroRNAs are recognized as important post-transcriptional regulators in plants. Information about the roles of miRNAs in common bean (Phaseolus vulgaris L.), an agronomically important legume, is yet scant. The objective of this work was to functionally characterize the conserved miRNA: miR398b and its target Cu/Zn Superoxide Dismutase 1 (CSD1) in common bean. We experimentally validated a novel miR398 target: the stress up-regulated Nodulin 19 (Nod19). Expression analysis of miR398b and target genes –CSD1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 74 publications
(130 reference statements)
5
82
1
Order By: Relevance
“…RNA preparations were used to detect mature miR172 in different plant tissues by low-molecular-weight RNA-gel hybridization using 15 mg of total RNA, as reported (Naya et al, 2014). Synthetic DNA oligonucleotides with antisense sequence corresponding to miR172 (59-ATGCAGCATCATCAA-GATTCT-39) and to U6 snRNA (59-CCAATTTTATCGGATGTCCCCG-39) were used as probes after radioactive labeling.…”
Section: Rna Isolation and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…RNA preparations were used to detect mature miR172 in different plant tissues by low-molecular-weight RNA-gel hybridization using 15 mg of total RNA, as reported (Naya et al, 2014). Synthetic DNA oligonucleotides with antisense sequence corresponding to miR172 (59-ATGCAGCATCATCAA-GATTCT-39) and to U6 snRNA (59-CCAATTTTATCGGATGTCCCCG-39) were used as probes after radioactive labeling.…”
Section: Rna Isolation and Analysismentioning
confidence: 99%
“…Common bean miRNAs that respond to drought, salinity, nutrient deficiencies, or metal toxicity stresses have been identified, and their target genes have been predicted or validated (Arenas-Huertero et al, 2009;Valdés-López et al, 2010;Contreras-Cubas et al, 2012). The roles of miR399 in the common bean root response to phosphorus deficiency (Valdés-López et al, 2008) and of miR398 in the regulation of copper homeostasis and response to biotic interactions (Naya et al, 2014) have been demonstrated. In this work, we analyzed the role of miR172 in common bean roots and nodules.…”
mentioning
confidence: 99%
“…In a recent research, it was observed that the expression level of miR398 decreased gradually in tomato leaves, after Phytophthora infestans (P. infestans) infection . Under pathogen attack, miR398 were down-regulated in several other plant species, while CSD1 and CSD2 were up-regulated, further detoxifying ROS (Jagadeeswaran et al 2009;Lu et al 2011;Naya et al 2014). Indeed, functional analyses have demonstrated that Nicotiana benthamiana (N. benthamiana) leaves transiently overexpressing miR398b were more susceptible to Sclerotinia sclerotiorum infection (Naya et al 2014).…”
Section: Mirnas and Host Defensementioning
confidence: 99%
“…Post-transcriptional gene regulation mediated by endogenous miRNAs play a crucial role in various aspects of plant development as well as adaptation to biotic and abiotic stresses (Naya et al 2014;Khraiwesh et al 2012;Paul et al 2011;Kundu et al 2017). In plants, mature miRNAs are generated from longer stem-loop RNA precursors (Pre-miRNA) with the aid of ribonuclease III-like Dicer (DCL1) enzyme (Fukudome and Fukuhara 2017).…”
Section: Introductionmentioning
confidence: 99%